Global, regional, and national burden of leukemia: Epidemiological trends analysis from 1990 to 2021 - Chengjun Hu; Weifeng Chen; Ping Zhang; Tongping Shen; Maozhong Xu (PLoS ONE, 2025)
Background: Leukemia is a prevalent form of cancer that encompasses four primary subtypes, posing significant health risks. Gaining insights into the global epidemiology of leukemia and its subtypes is crucial for effective resource allocation, clinical guidance, and scientific inquiry. Methods: From 1990 to 2021, we analyzed age-standardized rates (ASR) trends across 204 countries and territories, utilizing the estimated annual percentage change (EAPC). Results: In 2021, there were approximately 460,000 leukemia cases, 320,000 deaths, and 10.98 million disability-adjusted life years (DALYs). Globally, age-standardized incidence rates (ASIR), mortality rates (ASMR), and DALY rates are on the decline, while age-standardized prevalence rates (ASPR) are rising in high social demographic index (SDI) regions. Men experience a higher leukemia burden compared to women. By subtype, acute myeloid leukemia (AML), chronic myeloid leukemia (CML), and chronic lymphocytic leukemia (CLL) predominantly impact older individuals, while acute lymphoblastic leukemia (ALL) primarily affects children. Notably, leukemia ASIR and ASDR reductions are observed in countries with high human development index (HDI). Conclusion: Although there has been a marked decrease in global leukemia incidence, mortality, and DALYs over the past 31 years, the rise in new cases due to population growth suggests an increasing overall disease burden by 2050. Furthermore, the impact of leukemia varies significantly by region and country, highlighting the urgent need for innovative and personalized prevention and treatment approaches to mitigate this global health issue.